NBR and ethylene blends

By using rubber compositions of nitrile and ethylene terpolymers, especially blends of NBR and ethylene polymers, the need for synchronous belts in terms of medium to high temperature tolerance, oil resistance, flexibility and structural integrity, achieving efficient performance improvements.

CN119585182APending Publication Date: 2025-03-07THE GATES CORP
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202380055529.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-29
Filing Date
2023-06-28
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to find alternative HNBR materials to meet the requirements of synchronous belts at medium to high temperature tolerance, good oil resistance, flexibility as low as -40°C and high structural integrity.

Method used

A rubber composition is used which has a polymer blend of nitrile and ethylene terpolymer, in particular a blend of acrylonitrile-butadiene copolymer (NBR) and ethylene polymer, with a total composition of 30-50% by weight NBR and 20-40% by weight ethylene polymer, and organic peroxide or other accelerators are added therein.

Benefits of technology

Medium to high temperature tolerance, good oil resistance, flexibility as low as -40°C and high structural integrity are achieved, and the amount of reinforcement materials such as carbon black can be reduced while maintaining the desired properties of the synchronization belt.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

A rubber composition having a nitrile and ethylene terpolymer, in particular a polymer blend of an acrylonitrile-butadiene copolymer (NBR) and an ethylene polymer. The composition has an NBR in an amount of from 30 to 50% by weight of the total composition. In some embodiments, the ethylene polymer is an EPDM rubber, an ethylene acrylic elastomer, or a chlorinated polyethylene. The composition may include an organic peroxide or other accelerator. The rubber composition can be used for synchronous belts having medium temperature to high temperature resistance, good fuel resistance, flexibility as low as-40 DEG C, and high structural integrity. In addition, the rubber composition allows the amount of a reinforcing material such as carbon black to be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to compositions, in particular rubber compositions, for flexible belts such as timing belts having moderate to high temperature resistance, good oil resistance, flexibility down to -40°C, and high structural integrity. Background Art

[0002] HNBR is a hydrogenated form of NBR rubber, which is a synthetic rubber with very good temperature resistance and excellent oil resistance, and it is widely used in timing belt compounds to meet application requirements.

[0003] Alternative materials that meet the requirements of timing belt applications, including temperature and oil resistance, are desirable. Summary of the invention

[0004] This summary is provided to introduce a selection of concepts in a simplified form, which concepts will be further described in the detailed description below. This summary and the foregoing background technology are not intended to determine the key aspects or essential aspects of the claimed subject matter. In addition, this summary is not intended to be used to help determine the scope of the claimed subject matter.

[0005] The present invention relates to a rubber composition with a polymer blend of nitrile and ethylene terpolymer, particularly a composition with acrylonitrile-butadiene copolymer (NBR) and an ethylene polymer. The composition has 30-50% by weight of NBR of the total composition. In some embodiments, the ethylene polymer is an EPDM rubber (it is a well-known rubber made of ethylene, propylene and diene comonomers, which can be cross-linked via sulfur vulcanization). In other embodiments, the ethylene polymer is an ethylene acrylic acid elastomer. In yet other embodiments, the ethylene polymer is a chlorinated polyethylene. The composition may include an organic peroxide or other accelerators.

[0006] The rubber composition can be used for timing belts having moderate to high temperature resistance, good oil resistance, flexibility down to -40°C, and high structural integrity. In addition, the rubber composition allows for a reduction in the amount of reinforcing materials such as carbon black while maintaining the desired properties of the timing belt.

[0007] These and other aspects of the technology described herein will be apparent after considering the detailed description and drawings herein. However, it should be understood that the scope of the subject matter claimed should be determined by the issued claims, rather than by whether a given subject matter solves any or all of the problems mentioned in the background technology or includes any features or aspects described in the summary of the invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Non-limiting and non-exhaustive embodiments of the disclosed technology, including preferred embodiments, are described with reference to the following figures, wherein like reference numerals refer to like parts throughout the various figures unless otherwise specified.

[0009] Figure 1A It is the chemical structure of acrylonitrile butadiene rubber (NBR); Figure 1B It is a qualitative plot of the mechanical properties of NBR.

[0010] Figure 2A It is the chemical structure of EPDM with ethylidene norbornene (ENB) as the non-conjugated diene; Figure 2B It is a qualitative plot of the mechanical properties of EPDM.

[0011] Figure 3 It is a qualitative plot of the mechanical properties of NBR / EPDM blends.

[0012] Figure 4 It is a qualitative plot of the mechanical properties of HNBR.

[0013] Figure 5 is a perspective view of an exemplary tape made with the composition of the present invention. DETAILED DESCRIPTION

[0014] As shown, the present invention relates to a rubber composition having a polymer blend of nitrile and ethylene polymers, in particular, the composition has acrylonitrile-butadiene copolymer (NBR) and an ethylene polymer, wherein the NBR may be 30% to 50% by weight of the total blend, and the ethylene polymer may be 20% to 40% by weight of the total blend, and the remainder is ingredients such as activators, fillers, curing agents, reinforcing materials, anti-degradants (e.g., antioxidants, UV stabilizers), plasticizers, antistatic agents, colorants, processing aids, leveling agents, coagents, catalysts, etc.

[0015] The base polymer of the composition has abundant availability. The composition can be organic peroxide cured or accelerator cured. The cured composition can have a minimum Mooney viscosity of less than 60 MU when tested at 133°C. The composition has excellent adhesive strength, and a tensile strength greater than 18 MPa and temperature resistance up to 135°C, and retention of physical properties. The volume swelling rate of the cured composition in IRM 901 oil at 135°C for 168 hours is less than 20%; therefore, the composition has good oil resistance at high temperatures. In addition, the cured composition maintains flexibility at -35°C.

[0016] In the following description, reference is made to the accompanying drawings, which form a part of the description, and at least one specific implementation is shown by way of illustration. The following description provides other specific implementations. These embodiments are disclosed in sufficient detail to enable those skilled in the art to practice the present invention. It should be understood that other implementations can be conceived and performed without departing from the scope or spirit of the present invention. Therefore, the following specific embodiments should not be adopted in a restrictive sense. Although the present invention is not limited to this, an understanding of various aspects of the present invention will be obtained by the discussion of the embodiments (including the accompanying drawings) provided below. In some cases, a reference numeral may have an associated sub-label consisting of lowercase letters to represent one of a plurality of similar components. When a reference numeral is mentioned without specifying a sub-label, it is intended to refer to all of these multiple similar components.

[0017] The present invention relates to rubber composition, it has the polymer blend of nitrile and ethylene polymer, particularly acrylonitrile-butadiene copolymer (NBR) and ethylene polymer.The example of suitable ethylene polymer comprises EPDM rubber (it is the well-known rubber made by ethylene, propylene and diene comonomer, can be crosslinked via sulfur vulcanization), ethylene acrylic acid polymer or elastomer, and chlorinated polyethylene polymer.Composition has the NBR of 30-50 weight % of total composition.In some embodiments, composition comprises organic peroxide or other accelerator to add in curing.In addition, in some embodiments, composition comprises the non-conjugated diene of 15 weight % less than ethylene polymer weight.

[0018] The rubber composition is well suited for use in timing belts for automotive and industrial applications because the cured composition has moderate to high temperature resistance, good oil resistance, flexibility down to -40°C, and high structural integrity.

[0019] As shown, the composition includes a blend of acrylonitrile-butadiene copolymer (NBR) and an ethylene polymer, and optionally, less than 15% of a third monomer (a non-conjugated diene) by weight of the ethylene polymer.

[0020] Figure 1A shows the chemical structure of acrylonitrile butadiene rubber (NBR), and Figure 1B It is a qualitative plot of the mechanical properties of NBR. NBR has excellent mechanical properties, water resistance, oil resistance and solvent resistance. NBR has excellent low temperature resistance, but not high temperature resistance, however, the unsaturation present in the polymer backbone leads to poor ozone aging properties and heat aging properties. Therefore, blending NBR with other polymers can improve temperature resistance and ozone resistance.

[0021] Blends of NBR and ethylene polymers provide compositions with superior qualities to either material. For example, a composition of NBR and EPDM provides properties superior to either polymer alone.

[0022] Figure 2A shows the chemical structure of EPDM with ethylidene norbornene (ENB) as the non-conjugated diene, and Figure 2B is a qualitative plot of the mechanical properties of EPDM. EPDM has excellent temperature resistance (both low and high temperatures) and good water resistance, but poor oil and solvent resistance, even in its cured state. EPDM also has good heat aging and ozone properties.

[0023] The blend of NBR and EPDM is unexpected because it is well known that NBR and EPDM do not have good compatibility. NBR is a polar polymer due to the presence of acrylonitrile groups, while EPDM is a non-polar rubber. However, the presence of non-conjugated dienes in EPDM increases the compatibility of the two polymers by inducing some polarity in the ethylene propylene chain. The acrylonitrile content in NBR and the diene content in EPDM together promote good compatibility between the polymers. The composition blend has high tensile, elongation and tearing properties, which indicates that the compatibility between the polymers is improved.

[0024] The resulting blended composition of NBR and EPDM has a desirable balance of temperature and aging resistance, ozone resistance and solvent resistance. The composition also has sufficient flexibility at temperatures as low as -40°C, which is a general requirement for timing belts used in automotive and industrial applications. The composition also exhibits excellent adhesion when compounded with a selected adhesive.

[0025] Figure 3 is a qualitative plot of the mechanical properties of NBR / EPDM blends. It is seen that overall all properties of the blend are improved over the properties of the two polymers alone. The blend composition has excellent mechanical properties as well as water and oil resistance. The composition has good temperature resistance for both low and high temperatures.

[0026] Figure 4 It is a qualitative plot of the mechanical properties of HNBR, where NBR and ethylene polymer blends are its replacements. It is seen that the properties of the blended composition are comparable or close to those of HNBR.

[0027] Other ethylene polymers suitable for blending with NBR include ethylene acrylic elastomers, chlorinated polyethylene, ethylene propylene elastomers (EPM), ethylene butene (EBM), ethylene pentene, and ethylene octene (EOM).

[0028] The selection of polymer grade affects the flow characteristics of the blended compound. The high molecular weight grade with higher Mooney viscosity is undesirable for the synchronous belt of automotive application, because of poor fluidity and thus poor belt tooth (belt tooth) formation, but the final cured material (e.g. vulcanized rubber) has excellent physical properties such as tensile strength, modulus and elongation. On the other hand, low molecular weight grades promote flow, but the vulcanized rubber of blending may not have enough physical strength. There are many commercially available NBR grades with different molecular weights (e.g. Mw and Mn). These can be characterized by the Mooney viscosity (ML 1+4, at 100°C) of 30 to 90 MU of the polymer.

[0029] NBR polymers typically contain about 20% to about 50% by weight of acrylonitrile. The presence of acrylonitrile groups provides NBR with good solvent resistance, and this property can be further enhanced by selecting NBR containing more acrylonitrile. However, acrylonitrile groups reduce the cold flexibility of NBR and blended compositions. For example, NBR with 34% acrylonitrile content has a glass transition temperature close to -35°C. As the acrylonitrile content increases, the glass transition temperature also increases, which causes the cold flexibility of both NBR and blended compositions to decrease.

[0030] The amount of NBR and ethylene polymer is 25% to 75% by weight of the total weight of the raw material components forming the uncured blend composition, wherein NBR is 30% to 60% by weight of the total weight, and ethylene polymer is 10% to 30% by weight of the total weight. In some embodiments, NBR and ethylene polymer account for about 40% to 70% by weight of the total weight of the raw material components, and about 45-60% by weight in other embodiments.

[0031] The weight ratio of NBR to ethylene is from 3:1 to 1:1; in some embodiments, NBR and ethylene are present in a weight ratio of about 2:1.

[0032] Examples of suitable ethylene polymers for blending with NBR include EPDM, ethylene propylene elastomer (EPM), ethylene acrylic acid elastomer, chlorinated polyethylene, ethylene butene (EBM), ethylene pentene, and ethylene octene (EOM).

[0033] EPDM is a terpolymer comprising ethylene and propylene having a saturated polymer backbone and a saturated non-conjugated diene monomer and an ethylene-propylene copolymer. Examples of diene monomers present in EPDM are dicyclopentadiene (DCPD), ethylidene norbornene (ENB), 1,4-hexadiene and methylene norbornene.

[0034] EPDM typically contains about 30% to about 80% by weight ethylene and about 0% to about 15% non-conjugated diene. Typically, the diene content can be determined by an iodine value of about 5 to about 30. The Mooney viscosity (ML1+4 at 125°C) is typically about 40 to about 100 MU. Above 70% by weight ethylene, EPDM polymers exhibit crystalline characteristics.

[0035] In addition to NBR and ethylene polymers, the blend composition may include additional rubber raw materials including, but not limited to, any of natural rubber, styrene-butadiene rubber (SBR), chloroprene rubber (CR), hydrogenated nitrile rubber (HNBR), and fluoroelastomer (FKM).

[0036] The rubber stock (NBR, EPDM, and any others) is typically in the form of a solid powder, pellets, bales, or blocks, although in some embodiments it may be liquid or semi-liquid.

[0037] As mentioned above, the blend composition may include an organic peroxide or other accelerator to promote the curing of the blend composition. Various types of organic peroxides can be used together with the blend composition. Organic peroxides decompose at certain temperatures and produce free radicals, which trigger a crosslinking reaction in the compound. A specific example of an organic peroxide used with NBR and EPDM is α, α-bis (tert-butyl peroxide) diisopropylbenzene. In some embodiments, the total amount of organic peroxide is less than about 2.5% by weight of the raw material component.

[0038] Polymer compositions cured with organic peroxides exhibit higher heat resistance due to the formation of CC crosslinks between polymer chains. In contrast, sulfur-cured polymers form CSC or C-(S) x -C bond. The formation of monosulfide bonds (i.e., CS) or polysulfide bonds (i.e., SS) results in poorer heat resistance of the polymer. The CC bond energy (346 kJ / mol) is higher than the bond energies of both CS (272 kJ / mol) and SS (226 kJ / mol); this is reflected in the higher temperature resistance of peroxide-cured vulcanizates.

[0039] The blended composition may include various additives such as activators, fillers, curing agents, reinforcing materials, antidegradants (e.g., antioxidants, UV stabilizers), plasticizers, antistatic agents, colorants, processing aids, homogenizers, coagents, catalysts, etc. Typically, the total weight percent of additives is less than 65 weight percent of the raw material ingredients of the total composition, and in some embodiments less than 50 weight percent.

[0040] Examples of activators include stearic acid and zinc oxide. Stearic acid is generally solid and available as flakes or pellets with a specific gravity of about 0.85. Stearic acid contains iodine in an amount generally not exceeding 10% by weight. The acid number is 193 to 213. Zinc oxide is also solid, for example with a surface area of ​​4-6 m 2 / g and a fine powder with a specific gravity of 5.6. Some impurities may be present in the zinc oxide; for example, CuO <0.0005 wt%, MnO <0.0005 wt%, SiO2 <0.02 wt% and / or water-soluble salts <0.05 wt%. In some embodiments, the total amount of activator is less than about 5 wt% of the raw material ingredients, in some embodiments less than about 3 wt%. Long chain fatty (LCF) acids can be used as a leveling agent and can act as an activator when combined with zinc oxide.

[0041] Any suitable curing agent or material can be used, wherein the curing agent plays a promoting or auxiliary role during curing. Suitable exemplary curing agents include sulfur and peroxides. In some embodiments, the amount of the curing agent used is less than about 8 weight %, such as less than 5 weight %, of the total weight of the raw material ingredients.

[0042] Silica may be added to provide greater tensile strength, higher modulus, reduced compression set, and increased wear resistance to the blended composition. Silica is typically a solid such as a powder and may be treated or untreated. The surface area of ​​​​silica is typically 120-200 m 2 / g. The specific gravity of the exemplary treated silica treated with 5-8 wt % of organosilane is 1.9-2.0. The exemplary silica has a volatile content of 3-5% and a pH value of 6-8. The organosilane is a trialkoxysilane type. Therefore, the treated silica material has low hygroscopicity and significantly low volatile formation during mixing and processing. In some embodiments, the total amount of silica is about 10 wt % to 35 wt % of the raw material ingredients.

[0043] Carbon black and / or graphite may be used as fillers in rubber compounds.Examples of other fillers include metal oxides such as aluminum oxide, magnesium oxide, copper oxide, and zinc oxide, clay, montmorillonite clay, pulp, and mica.

[0044] The raw materials of the blend composition may include reinforcement materials such as chopped fiber segments, although other reinforcement materials such as elongated segments, fibers or nanotubes may also be used. Whether the reinforcement material is chopped or elongated, it may be, for example, aramid, polyester (PET), cotton, nylon, glass, carbon fiber rope, hybrid rope, metal, ceramic and other plastics. The reinforcement material may be made of organic materials or synthetic materials, or a mixture of organic materials and synthetic materials.

[0045] The size of the reinforcing material is generally not limited. In some embodiments, the chopped fibers have a high aspect ratio, and their length is 0.2 mm to 3 mm. In some embodiments, the reinforcing material (e.g., chopped fibers or elongated materials) has an aspect ratio of 10 to 250. In some embodiments, the amount of the reinforcing material is 5% to 30% by weight of the total weight of the raw material ingredients. The reinforcing material is mixed with the raw material ingredients, and the resulting band has a reinforcing material uniformly dispersed throughout the blended composition.

[0046] In some embodiments, the amount of filler (including any silica, carbon black or carbon reinforced fiber) is 5% to 45% by weight of the total weight of the raw material ingredients, and in other embodiments, the filler is about 10% to about 20% by weight of the total weight of the raw material ingredients. The polymer blend of NBR and ethylene polymer allows the amount of carbon reinforced fiber or other carbon to be reduced, and the amount of other fillers to be increased, while still obtaining acceptable properties of the synchronous belt. In some embodiments, the ratio of silica to reinforced carbon is 5: 1 to 3: 1, for example about 4: 1.

[0047] Polymers degrade when exposed to different types of environmental factors, including oxygen, heat / temperature, UV light, weathering, catalytic degradation due to heavy metal ions, dynamic fatigue, etc. Failures observed in rubber compounds due to environmental degradation include loss of elasticity and tensile strength, formation of cracked surfaces, and the appearance of cracks. The presence of unsaturation in polymers can increase the tendency to fail due to thermal aging due to the allyl CH bonds in the unsaturated chemical structure. Among the different types of CH bonds (primary, secondary, tertiary), the bond energy of allyl CH is the weakest. This factor promotes the formation of free radicals and peroxy radicals in the presence of oxygen and heat and causes chain scission. Once the polymer backbone is broken, the compound begins to lose its physical and mechanical strength and begins to degrade. Antioxidants act as free radical sinks; they scavenge free radicals to prevent polymer chain scission and increase the service life of the resulting product.

[0048] An antioxidant that can be used in rubber compounds, especially with NBR, NR, BR and SBR compounds, is a polymeric quinoline derivative, 1,2-dihydro-2,2,4-trimethylquinoline. Another antioxidant is a condensate of an alkylated imidazole and a diarylamine or ketone, and another is a condensate of mercaptobenzimidazole and diphenylamine / acetone; these are strong, non-staining antioxidants for natural and synthetic rubbers, and provide excellent temperature and flex protection at elevated temperatures.

[0049] Plasticizers can be added to elastomeric compounds for various reasons, such as to increase softness or flexibility, to lower the glass transition temperature, to reduce crystallization, to increase dispersion, or to reduce the cost of the compound. Common plasticizers used in elastomeric compounds are mineral oils and esters, such as phthalates, sebacates, and adipates. NBR is compatible with various types of ester plasticizers, including adipates, phthalates, trimellitates.

[0050] Dialkyl esters and dioctyl adipate (DOA) are highly efficient plasticizers that can be used to impart excellent low temperature flexibility and impact resistance to compounds. In addition to their high efficiency and contribution to low temperature properties, they are chemically stable and resist discoloration upon prolonged exposure to temperature and UV light. The combination of low viscosity and efficiency provides excellent dry mixing and processing characteristics.

[0051] Microcrystalline wax can be added as a physical antiozonant for unsaturated rubbers. Polymer chains containing double bonds are susceptible to ozonolysis reactions and chain scission in the presence of ozone. Microcrystalline wax provides a shield or barrier on the compound and protects it from degradation caused by chain scission.

[0052] Modified resorcinol, which is a resorcinol formaldehyde homopolymer resin modified with selected groups, can be used as a precondensed dry binder; chemically, it is a resorcinol formaldehyde homopolymer resin modified with selected groups. The modified resorcinol promotes homogeneity of the blended composition.

[0053] Metal acrylates such as zinc dimethacrylate can be used to improve the physical and mechanical properties of the compound and act as a co-agent. In the presence of organic peroxides, the metal co-agent forms ionic bonds and improves the tear strength, modulus and flexural resistance of the compound.

[0054] (with maleic anhydride) modified polybutadiene can be used as an adhesion promoter in the vulcanized rubber of peroxide curing.Chemically, it is a low molecular weight, low vinyl butadiene functionalized with maleic anhydride.Anhydride functional groups can react with epoxy, amine and hydroxyl groups, which can produce unique adhesives, sealants, encapsulants and coatings.It also improves the compatibility of non-polar elastomers such as EPDM, and increases the adhesion of peroxide cured elastomers to polyester, aramid or metal substrates.

[0055] Substituted phenolic derivatives such as 2,6-di-tert-butyl-N,N-dimethylamino-p-cresol can be used as scorch inhibitors for peroxide cure systems. They initially form adducts to trap free radicals from the peroxide and affect the processing and flow time of the compound.

[0056] The above-mentioned elastomer (NBR and ethylene polymer) and any other ingredients can be blended by conventional rubber blending methods. In some embodiments, mixing is usually carried out using an industrial mixer such as a Banbury mixer to mix all raw material ingredients together; however, other mixing techniques and methods can be used. For example, a roller mill and a banbury mixer can be used. In some embodiments, each raw material ingredient is added to the mixer in a specific order to ensure that the raw material ingredients are fully incorporated and dispersed. In some embodiments, some raw material ingredients can be mixed together and then added to the mixture in order.

[0057] Tables 1 and 2 provide exemplary ingredient ranges for blend compositions according to the present invention.

[0058] Table 1

[0059] Table 2

[0060] The resulting compositions from Table 1, Table 2, or any of the above may be used to form belts, such as timing belts for automotive applications. Figure 5 A universal belt 500 is shown having a body 502 formed of a flexible material, having a back side 504 and a front side 506, with a plurality of load ropes 508 within the body 502, this particular rope 508 being bundled in three bundles, although in other embodiments the ropes 508 may be a single rope or bundled in other ways. The ropes 508 may be, for example, carbon ropes, polymer ropes (e.g., polyester, aramid), fiberglass ropes, etc. Defined in the front side 506 are a plurality of teeth 510; Figure 5 The teeth 510 are trapezoidal in shape, but the tooth shape is not limited thereto and may take any shape compatible with a sprocket, gear, or other belt gear. Each individual tooth 510 extends perpendicular to the longitudinal length of the belt 500, so that a plurality of teeth 510 extend along or around the length of the belt 500. In use, the teeth 510 on the front side 106 contact a drive mechanism such as a gear or sprocket. Although in Figure 5 It is not shown in FIG. 5 , but the belt 500 is an endless belt having the form of a loop without a start point and an end point.

[0061] Example

[0062] The objects and advantages of the present invention are further illustrated by the following non-limiting examples. The specific materials and amounts thereof and other conditions and details cited in these examples should not be construed as excessively limiting the present invention. Unless otherwise stated, all parts, percentages, ratios, etc. in the embodiments and the remainder of the present invention are by weight.

[0063] Example 1

[0064] The materials listed in Table 3 were used in the amounts listed (in grams) to prepare a first blended composition according to the present invention.

[0065] Table 3

[0066] The specific gravity of the semi-reinforcement carbon black is 1.8, the DBP absorption rate is 30-48 CC / 100g, the iodine absorption rate is 6-12 mg / g, the maximum heat loss is 1%, the 325 mesh sieve residue is 0.1%, the ash content is less than 0.5%, and the pellet hardness is 30 g.

[0067] Precipitated silica has a specific gravity of 2.0 and is a fine white, odorless powder. The BET surface area of ​​silica is 130-200 m 2 / g. The drying loss (105℃, 2 hours) is 3-7%. The ignition loss (1000℃, 2 hours) when anhydrous is 6% at most. The pH of 5% water slurry is 6-8, the SiO2 hydrate % is minimum 87%, and the DBP absorption value is 200-280 mL (based on 100 g).

[0068] The specific gravity of the treated silica used is 1.9-2.0. The trialkoxysilane treatment content is 5-8%. The volatile content in the treated silica is 3-5%, the pH value is 6-8, and it appears as a white powder. The specific surface area of ​​this silica grade is 120-150 m 2 / g.

[0069] Zinc oxide is an odorless white fine powder with a specific gravity of 5.6 and a surface area of ​​4-6 m 2 / g. The heat loss value of this grade at 110°C is maximum 0.5%. The ash content of this grade is 99%, the wet sieve residue (% retained on #325 mesh sieve) does not exceed 0.05 and (% retained on #200 mesh sieve) is less than 0.02. The presence of CuO < 0.0005%, MnO < 0.0005%, SiO2 < 0.02% and water-soluble salts < 0.05%.

[0070] The mixing of ingredients was done in three stages. In the first stage, all materials except the curing agent were charged into the mixture at an RPM of 10-20. The total mixing time was 8-12 minutes to a pouring temperature of 150°C. In the second stage, the compound was mixed again to 150°C to achieve better dispersion and uniformity. The peroxide curing agent was added in the third stage of mixing, where the RPM was maintained at 8-10 and the batch was poured at 95°C.

[0071] The mixed raw materials were cured at 180° C. for 20 minutes using a hydraulic press.

[0072] The physical properties of the cured panels were determined using stress-strain testing, which yielded tensile strength, modulus, elongation (ASTM D412), tear test (ASTM D624), Shore A hardness (ASTM D2240), volume swell in IRM 901 at 135°C for 168 hours (ASTM D471), compression set at 135°C for 168 hours (ASTM D395).

[0073] The ozone test was performed by placing dumbbell-shaped specimens under tension (20% and 30%) in an ozone chamber containing 50 ppm of ozone at 40°C. After certain time intervals, the specimens were investigated at 7x magnification for any cracks.

[0074] Cold flexibility was tested by placing strips of the cured compound (dimensions: 6" x 1" x 0.75") in a -35°C cold room for 24 hours and then bending the specimen at an angle of 180° after the specified conditioning time was complete.

[0075] The results of the above tests are listed in Table 4.

[0076] Table 4

[0077] Cured plaques of the NBR / EPDM blend compounds were used to make test timing belts, which were subjected to a series of static tests. Table 5 shows a comparison between a control belt made with the prior art compound and a test belt made with the NBR / EPDM blend compound of Table 3.

[0078] Table 5

[0079] Example 2

[0080] Another blend composition according to the present invention was prepared using the materials listed in Table 6 in the amounts listed (in grams).

[0081] Table 6

[0082] Example 2 was subjected to the same tests as Example 1, and the results are provided in Tables 7 and 8 below.

[0083] Table 7

[0084] Table 8

[0085] From the foregoing it will be appreciated that specific embodiments of the invention have been described herein for purposes of illustration, but that various changes may be made without departing from the scope of the invention. Accordingly, the invention is not to be limited, except in the context of the appended claims.

[0086] Although the technology has been described in language specific to certain structures and materials, it should be understood that the invention defined by the appended claims is not necessarily limited to the specific structures and materials described. Instead, specific aspects are described in the form of implementing the claimed invention. Because many embodiments of the present invention can be practiced without departing from the spirit and scope of the present invention, the present invention is present in the following appended claims.

[0087] Unless otherwise stated, all numbers or expressions used in the specification (except for the claims), such as those expressing dimensions, physical properties, etc., are understood to be modified by the term "about" in all cases. At the very least, and without attempting to limit the application of the doctrine of equivalents of the claims, each numerical parameter modified by the term "about" recorded in the specification or claims should be interpreted at least according to the number of significant figures recorded and by applying rounding techniques. In addition, the full range disclosed herein should be understood to cover the claims and provide support for the claims, which record any and all sub-ranges or any and all single values ​​contained therein. For example, the range of 1 to 10 should be considered to include and provide support for the claim, which describes any and all sub-ranges or single values ​​between and / or including the minimum value 1 and the maximum value 10; that is, all sub-ranges starting with a minimum value of 1 or greater and ending with a maximum value of 10 or less (e.g., 5.5 to 10, 2.34 to 3.56, etc.) or any value from 1 to 10 (e.g., 3, 5.8, 9.9994, etc.).

Claims

1. A timing belt formed from an uncured composition comprising acrylonitrile butadiene rubber (NBR) and an ethylene polymer, said NBR and ethylene polymer being present in an amount of 25 to 75 wt % of said uncured composition.

2. The tape formed from the uncured composition of claim 1, wherein the NBR is present at 30 to 60 wt% of the uncured composition, and the ethylene polymer is present at 10 to 30 wt% of the uncured composition.

3. The tape formed from the uncured composition of claim 1, wherein the NBR is 30% to 50% by weight of the uncured composition.

4. The tape formed from the uncured composition of claim 1, further comprising an organic peroxide.

5. The tape formed from the uncured composition of claim 1, wherein the ethylene polymer is an ethylene-propylene-diene terpolymer (EPDM).

6. The tape formed from the uncured composition of claim 1 wherein the ethylene polymer is an ethylene acrylic elastomer.

7. The tape formed from the uncured composition of claim 1 wherein the ethylene polymer is chlorinated polyethylene.

8. A tape formed from an uncured composition according to claim 1, further comprising a carbon reinforcing filler and silica.

9. A tape formed from an uncured composition according to claim 8, wherein the silica is present at a level greater than the carbon reinforcing filler.

10. The tape formed from the uncured composition of claim 9, wherein the silica is present at a level of about 10% to 35% by weight of the uncured composition, and the carbon reinforcing filler is present at a level of about 3% to 8% by weight.

11. The tape formed from the uncured composition of claim 9, wherein the silica is present in a ratio of about 4:1 relative to the carbon reinforcing filler.

12. The tape formed from the uncured composition of claim 1, wherein the tape has a tensile strength of 18 MPa or greater.

13. The tape formed from the uncured composition of claim 1, wherein the tape is easily bendable at -35°C.

Citation Information

Cited By

  • Vibrating diaphragm for sound production device, sound production device and electronic equipment

    CN120602854A

  • Diaphragm for sound production device, sound production device, and electronic device

    CN120602854B